Administración de riesgos en proyectos de construcción de túneles (2012)
This thesis, aimed to identify the risks involved in building an infrastructure project, in this case the tunnels, and a matrix in which they were given a score and treatment -- To fulfill these objectives, several visits were done to various projects where there were building tunnels -- The interview was used as a technique for collecting information for later analysis -- The sample projects were el Tunel Aburrá-Oriente and el Interceptor Norte -- Both projects include the construction of tunnels but with different methods -- El Tunel Aburrá-Oriente will be constructed using drilling and blasting while el Interceptor Norte will be done by the micro tunneling method